PENDAMPINGAN TADARUS AL-QUR'AN BAGI ANAK USIA SD/MI DI MASJID TANWIRUL HUDA - Siti Kumairo' Yili Al Manik; Aghitsna Nasya Adilla (P3M STAI KH. MUHAMMAD ALI SHODIQ, 2025)
Abstract: Quran recitation mentoring for MI/SD children at the Tanwirul Huda Mosque located in Purwokerto Srengat Blitar Village during the month of Ramadan aims to improve the quality of reading, understanding of tajweed, as well as character building and discipline. The Participatory Action Research (PAR) method is applied so that participants are actively involved in all stages of the program, starting from observation, reflection, planning, to ongoing action. This activity is carried out every afternoon from 15.30 to 17.35 WIB, adjusting to children's free time after school and filling their free time before breaking the fast. The results of the mentoring show an increase in reading fluency, understanding of tajweed, and children's confidence in recitation. In addition, this program also reduces the habit of children playing with cellphones and increases their participation in religious activities. However, there are challenges such as differences in the ability to read the Quran and a decrease in children's enthusiasm after several days of participating in the program. As a solution, improvements are made through a simple tajweed module, dividing small groups according to ability, and providing appreciation to increase motivation. With continuous evaluation and improvement, this program will not only become an effective medium for learning the Qur'an, but will also help shape a generation that loves and practices the Qur'an more in everyday life.